Hypusine modification for growth is the major function of spermidine in Saccharomyces cerevisiae polyamine auxotrophs grown in limiting spermidine - Chattopadhyay, Manas K. (National Academy of Sciences, 2008)
Spermidine and its derivative, hypusinated eIF5A, are essential for the growth of Saccharomyces cerevisiae. Very low concentrations of spermidine (10(−8) M) are sufficient for the growth of S. cerevisiae polyamine auxotrophs (spe1Δ, spe2Δ, and spe3Δ). Under these conditions, even though the growth rate is near normal, the internal concentration of spermidine is <0.2% of the spermidine concentration present in wild-type cells. When spe2Δ cells are grown with low concentrations of spermidine, there is a large decrease in the amount of hypusinated eukaryotic initiation factor 5A (eIF5A) (1/20 of normal), even though there is no change in the amount of total (modified plus unmodified) eIF5A. It is striking that, as intracellular spermidine becomes limiting, an increasing portion of it (up to 54%) is used for the hypusine modification of eIF5A. These data indicate that hypusine modification of eIF5A is a most important function for spermidine in supporting the growth of S. cerevisiae polyamine auxotrophs.